Optimasi Sterilisasi Eksplan Biji Manggis (Garcinia mangostana L.) Menggunakan Natrium Hipoklorit Secara In vitro - Harahap, Fauziyah; Asri, Elita; Hasairin, Ashar; Edi, Syahmi; Suriani, Cicik; Daulae, Abdul Hakim; Panggabean, Nurul Huda (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study evaluates the effects of NaOCl concentration and immersion time on contamination levels and viability of in vitro mangosteen seed explants, aiming to identify the optimal sterilization protocol. Conducted at YAHDI Tissue Culture Laboratory, Medan, Indonesia, a Randomized Complete Block Design tested three treatment combinations: (1) 15% and 10% NaOCl for 5 minutes, (2) 20% and 15% NaOCl for 15 minutes, and (3) 30% and 20% NaOCl for 25 minutes. After immersion, explants were rinsed three times with sterile distilled water. Observations spanned 12 MST, with data analyzed using ANOVA and Games-Howell post hoc tests; contamination sources were qualitatively described. Results showed the first combination had the lowest effectiveness, the second was better but suboptimal, while the third significantly delayed contamination and yielded the highest explant survival rate of 86.1%. The third treatment also prolonged the contamination-free period compared to others. Fungal and bacterial contaminants were predominant, highlighting the need for effective disinfectants against both. These findings indicate that the third combination is a promising sterilization protocol for mangosteen seed explants, especially for hard endocarp tissues prone to contamination.